2021
DOI: 10.1177/2325967120979994
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Foot and Ankle Abnormalities in Elite Professional Soccer Players

Abstract: Background: Professional soccer players are often evaluated with asymptomatic lesions of the ankle and foot, and such abnormalities may eventually become clinically relevant. Purpose: To ascertain the prevalence of foot and ankle abnormalities in elite professional adult soccer players. Study Design: Case series; Level of evidence, 4. Methods: Professional adult male elite soccer players (n = 37) underwent magnetic resonance imaging (MRI) scans of both their feet and ankles. All competed for their respective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Thus, any abnormal alignment of the ankle would lead to local stress concentration and accelerate the degeneration of ankle cartilage [ 2 , 3 ]. Many studies have shown that patients with repeated sprains or fractures of the ankle have a high probability of talar cartilage injury [ 4 , 5 ]. In the early stages of talar cartilage injury, there are no obvious signs and the pain is diffuse and poorly localized; in the late stages, the main clinical manifestations are ankle swelling and pain (aggravated during weight-bearing walking) and joint strangulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any abnormal alignment of the ankle would lead to local stress concentration and accelerate the degeneration of ankle cartilage [ 2 , 3 ]. Many studies have shown that patients with repeated sprains or fractures of the ankle have a high probability of talar cartilage injury [ 4 , 5 ]. In the early stages of talar cartilage injury, there are no obvious signs and the pain is diffuse and poorly localized; in the late stages, the main clinical manifestations are ankle swelling and pain (aggravated during weight-bearing walking) and joint strangulation.…”
Section: Introductionmentioning
confidence: 99%
“…The participants had a mean BMI of 22.54 ± 3.07 (range: 18.61–36.55) kg/m 2 . The BIA revealed a mean FMI, mean FFMI and SMM/height 2 of 4.38 ± 1.77, 18.16 ± 2.51 and 8.59 ± 1.55 kg/m 2 , respectively. The mean hours of physical activity per week were 4.78 ± 3.02 (range: 1.00–15.00) h. Although the participants were asked not to perform any physical activity 48 h prior the study, two individuals reported medium level of physical activity.…”
Section: Resultsmentioning
confidence: 94%
“…Tetrapolar, single-frequency (5 kHz) impedance measurements were taken to acquire fat mass (FM), fat-free mass (FFM) and skeletal muscle mass (SMM). Values were divided by height squared creating the fat mass index (FMI), fat-free mass index (FFMI) and skeletal muscle mass/height 2 (SMM/height 2 ) for height adjustment. 10 , 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations